THE INFLUENCE OF PIECE-RATE WAGES, MOTIVATION, AND LEADERSHIP STYLE ON THE EMPLOYEES’ PERFORMANCE AT PABRIK PENGOLAHAN KARET ZEELANDIA- PT PERKEBUNAN NUSANTARA I - Handoko (LPPM Institut Teknologi dan Sains Mandala, 2025)
The objective of this study was to determine simultaneously and partially the influence of piece-rate wages, motivation, and leadership style on the employee’s performance of Pabrik Pengolahan Karet Zelandia PT Perkebunan Nusantara I. This study uses a quantitative approach with explanatory research. The population in this study was 49 employees at Pabrik Pengolahan Karet Zeelandia- PT Perkebunan Nusantara I. The method of determining the sample used total sampling, in which all 49 employees were sampled in this study. The data in this study were mainly obtained by using questionnaires. Based on statistics analysis, it is proved that: 1) Simultaneously, there is a significant influence of piece-rate wages, motivation, and leadership style on the employees’ performance, 2) Partially, there is significant influence of piece-rate wages on the employees’ performance, 3) Partially, there is significant influence of motivation on the employees’ performance, 4) Partially, there is significant influence of leadership style on the employees’ performance, 5) Leadership style is the variable that makes the greatest contribution to the performance of employees at Pabrik Pengolahan Karet Zeelandia PT Perkebunan Nusantara I. Keywords: piece-rate wages, motivation, and leadership style, employees’ performance